Systematics within Gyps vultures: a clade at risk - Rasmussen Pamela C; Lerner Heather RL; Johnson Jeff A; Mindell David P (BMC Evolutionary Biology, 2006)
Abstract Background Populations of the Oriental White-backed Vulture (Gyps bengalensis) have declined by over 95% within the past decade. This decline is largely due to incidental consumption of the non-steroidal anti-inflammatory veterinary pharmaceutical diclofenac, commonly used to treat domestic livestock. The conservation status of other Gyps vultures in southern Asia is also of immediate concern, given the lack of knowledge regarding status of their populations and the continuing existence of taxonomic uncertainties. In this study, we assess phylogenetic relationships for all recognized species and the majority of subspecies within the genus Gyps. The continuing veterinary use of diclofenac is an unknown but potential risk to related species with similar feeding habits to Gyps bengalensis. Therefore, an accurate assessment of the phylogenetic relationships among Gyps vultures should aid in their conservation by clarifying taxonomic uncertainties, and enabling inference of their respective relatedness to susceptible G. bengalensis. Results Phylogenetic results using mitochondrial cytB, ND2 and control region sequence data indicate a recent and rapid diversification within the genus Gyps. All recognized species formed monophyletic groups with high statistical support, with the exception of the Eurasian Vulture, for which specimens identified as subspecies G. fulvus fulvescens appear closely related to the Himalayan Vulture (G. himalayensis). In all analyses, the earliest divergence separated the Oriental White-backed Vulture from other Gyps taxa, with the next diverging taxon being either the African White-backed Vulture (G. africanus), or the Himalayan Vulture. All analyses supported a sister relationship between the Eurasian Vulture (G. f. fulvus), and Rüppell's Vulture (G. rueppellii), with this clade being sister to another consisting of the two taxa of "Long-billed" Vulture (G. indicus indicus and G. i. tenuirostris), and the Cape Vulture (G. coprotheres). These molecular phylogenies strongly support the treatment of indicus and tenuirostris as separate species, as does morphological data showing that these two taxa of similar overall size differ in proportions, especially in rostral, alar, and pedal characters. In addition, grouping of bengalensis and africanus together in the genus Pseudogyps, as historically proposed, is not upheld based on mitochondrial data. Conclusion Both molecular and morphological data provide strong support for considering the "Long-billed" Vulture to be comprised of two species (G. indicus and G. tenuirostris), and further analysis is warranted to determine the taxonomic distinctiveness of G. f. fulvescens. Our phylogenetic analyses and conservative estimates suggest the diversification of Gyps taxa to be within the past 6 million years. Diclofenac susceptibility has been previously demonstrated for four Gyps species (G. indicus, G. fulvus, G. africanus, G. bengalensis), and the phylogenetic position of these species each forming a sister relationship with at least one of the remaining species, support concern that other Gyps taxa may be susceptible as well. Determining genetic and evolutionary distinctiveness for Gyps lineages is increasingly important as a breeding program is being established to prevent extinction.